Prescription drug monitoring programs in the US: A systematic literature review on its strength and weakness - Fahd Alogaili; Norjihan Abdul Ghani; Nordiana Ahmad Kharman Shah (Elsevier, 2020)
Prescription Drug Monitoring Program (PDMP) is an electronic database that tracks the prescriptions of controlled drugs with its aims to combat the incidence of drug abuse. Although the establishment of PDMP in the US was since 2003, evidence of the impact of PDMP's strength and weakness towards its implementation is still scarce. A systematic literature review according to Preferred Reporting Items for Systematic Review (PRISMA) standard was conducted to investigate the influence of PDMP's strength in combating the incidence of drug abuse and also to review the weaknesses of PDMP that prohibit its implementation. Results from this study reveal that the implementation of PDMP has mitigated the issue of drug abuse and has increased work efficiency among healthcare practitioners. However, the implementation rate of this system is low due to its weaknesses such as limited internet access and limited access to the PDMP system. Therefore, efforts to overcome the weaknesses of PDMP need to be instituted to ensure the healthcare system could fully optimize PDMP's benefits.